Design and Study of Strip-Slot Waveguide Structure for Dispersion Analysis - Nandam Ashok; Yeung Lak Lee; WooJin Shin (IEEE Photonics Journal)
We propose a slot waveguide design for dispersion compensation at the wavelength of 1500 nm. The proposed structure is based on coupled strip slot waveguide. A strong interaction between strip and slot-waveguide modes has been utilized to achieve high dispersion at the desired wavelength. Numerical analysis of the structure has been carried out by the finite difference time domain (FDTD) method. Present design shows a high negative dispersion of $-7.3× 10^{4}\ \text{ps/km-nm}$ over a full width at half maximum of 22 nm. The resonance wavelength of structure can be fine tuned by varying the strip and slot waveguide thickness. Strip-slot separation has been utilized to tune the magnitude of dispersion. Such a structure should find applications in the design of integrated-optic dispersion compensators for optical telecommunication and ultrafast waveguide lasers.